Implications of the digital divide: A systematic review of its impact in the educational field - Sebastián Miras; Mónica Ruiz-Bañuls; Isabel María Gómez-Trigueros; Copelia Mateo-Guillen (Journal of Technology and Science Education, 2023)
Previous research has shown the consolidation of the digital divide as an object of study over the last two decades. The pandemic caused by COVID-19 has multiplied the consequences of digital exclusion, as well as the number of studies examining its effects in the educational field. Based on this current educational reality, we approach a proposal that examines in depth the existing literature on the digital divide in the educational context by using the systematic review as a research methodology. We present an analysis of relevant studies published in the last three years with the aim of answering the following questions: How did the digital divide affected e-learning and ICT implementation during the pandemic? ; what methods were used to assess it? ; and what are the proposals to counteract its presence?. The results obtained in our study confirm the use of systematic reviewing which synthesize and accumulate the results of different primary studies. These results also serve to identify research gaps that point, in our case, towards future lines of work on the causes, persistence and interventions to mitigate the expansion of the digital divide in today's educational landscape.